TRANSACTION COST THEORY IN DIGITAL, COLLABORATIVE, AND EMERGING MARKET CONTEXTS: A SYSTEMATIC LITERATURE REVIEW (2020–2025) - Lydia Yuntika; Sambas Ade Kesuma; Iskandar Muda; Firman Syarif (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study conducts a systematic literature review of recent applications of Transaction Cost Theory (TCT) in digital, collaborative, and emerging market contexts between 2020 and 2025. Using Scopus-indexed journal articles screened through a PRISMA-guided process, this review synthesizes how TCT has been employed to explain organizational behavior amid technological transformation, inter-organizational collaboration, and institutional complexity in developing economies. The findings reveal that digital technologies reshape transaction costs by reducing traditional search, negotiation, and monitoring costs while introducing new risks associated with data governance, cybersecurity, and algorithmic oversight. The literature also highlights how collaboration in supply chains, international business, and interfirm alliances depends on hybrid governance mechanisms that combine relational and formal controls. In emerging markets, institutional voids, corruption risks, and legitimacy pressures further influence governance choices and transaction costs. This review identifies key research gaps related to digital auditing, sustainability governance, and cross-country comparisons, offering a future research agenda for expanding TCT in contemporary organizational landscapes.